2012
DOI: 10.5653/cerm.2012.39.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers for predicting pregnancy outcome in women undergoing IVF: human chorionic gonadotropin, progesterone, and inhibin A level at 11 days post-ET

Abstract: ObjectiveThis study was performed to assess the prognostic value of serum hCG, progesterone, and inhibin A levels measured at 11 days post-ET for predicting pregnancy outcome in women participating in IVF.MethodsBetween May 2005 and April 2008, sera were obtained from 70 infertile women who underwent IVF-ET at 11 days post-ET and stored. HCG, progesterone, and inhibin A levels were measured by commercial enzyme-linked immunosorbent assay kits. The predictive accuracy of hCG, progesterone, and inhibin A levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
5
12
0
3
Order By: Relevance
“…The subjects showed a mean β -hCG level of 157.3±79.5 mIU/mL and a mean progesterone level of 29.9±17.4 ng/mL 14 days after oocyte retrieval, which is similar with those of previous reports [1618]. In the comparison of the β -hCG and progesterone levels, significantly higher levels were shown in the ongoing pregnancy maintenance group than in the miscarriage group, which is also consistent with those of previous studies [1618]. A previous study revealed that patients with repeated miscarriages showed significantly decreased hCG and progesterone secretion compared to healthy controls [19].…”
Section: Discussionsupporting
confidence: 90%
“…The subjects showed a mean β -hCG level of 157.3±79.5 mIU/mL and a mean progesterone level of 29.9±17.4 ng/mL 14 days after oocyte retrieval, which is similar with those of previous reports [1618]. In the comparison of the β -hCG and progesterone levels, significantly higher levels were shown in the ongoing pregnancy maintenance group than in the miscarriage group, which is also consistent with those of previous studies [1618]. A previous study revealed that patients with repeated miscarriages showed significantly decreased hCG and progesterone secretion compared to healthy controls [19].…”
Section: Discussionsupporting
confidence: 90%
“…The median value was higher in successfully delivered (572 IU/L) and ongoing (977 IU/L) pregnancies compared to nonviable pregnancies (174 IU/L) which was similar to the results reported earlier. [1345151617182125262728] The levels of day 14 βhCG was found to be significantly higher in women with higher order pregnancies compared to those with singletons ( P < 0.01), which is similar to studies reported in literature. [12478914161929] The present study is unique as it defines the cutoff value of βhCG as early as day 14 post ET.…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that βhCG has more predictive value than other biochemical markers for predicting and assessing pregnancy outcome. [1511] Our data also shows that there were significant differences in the value of βhCG levels studied 14 days post ET in women with viable versus nonviable pregnancies. The median value was higher in successfully delivered (572 IU/L) and ongoing (977 IU/L) pregnancies compared to nonviable pregnancies (174 IU/L) which was similar to the results reported earlier.…”
Section: Discussionsupporting
confidence: 56%
“…The classifications of pregnancy outcomes were the same as previously described [14,15]. Clinical pregnancy was confirmed by the presence of a gestational sac observed on ultrasound scans, and clinical abortion was defined by pregnancy failure after the gestational sac confirmed.…”
Section: Definitions Of the Outcome Measuresmentioning
confidence: 99%